Tubular adenoid cystic carcinoma of palate: A rare case report - Deepanshu Garg; Mysore Kantharaja Sunil; Ashwarya Trivedi; Deepika Kapoor (Wolters Kluwer Medknow Publications, 2015)
Adenoid cystic carcinoma (ACC) is a rare malignant tumor that affects the major and minor salivary glands, the lacrimal glands, the ceruminous glands and occasionally the excretory glands of the female genital tract. 30-40% of these carcinomas occur in the head and neck region. Approximately 50-70% of the cases have been reported in the minor salivary glands. The most common location is the palate, generally in the area of the greater palatine foramen. ACC is generally characterized by a slow growth rate, and it is often present for several years before the patient seeks treatment. Here we present a case of 42-year-old female who came to the department for the complaint of a swelling over the right side of palate since 2-3 months which was diagnosed as a benign tumor initially, but was confirmed as tubular ACC histologically.